2018
DOI: 10.1097/ccm.0000000000003134
|View full text |Cite
|
Sign up to set email alerts
|

Markedly Deranged Injury Site Metabolism and Impaired Functional Recovery in Acute Spinal Cord Injury Patients With Fever

Abstract: Early after spinal cord injury, fever is associated with more deranged injury site metabolism than normothermia and worse prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Fever was particularly detrimental on injury site metabolism when the peripheral white cell count was high, which suggests that fever associated with infection may be more detrimental than neurogenic fever. In 2 TSCI patient cohorts, managed in London and Berlin [57], high fever burden correlated with less neurological improvement. Though further studies are required to determine the effect and temporal relations between the different types of fever (infection, neurogenic) and injury site metabolism, based on the data to date, we suggest prompt treatment of fever in TSCI patients with paracetamol, nonsteroidal anti-inflammatory drugs, or active cooling.…”
Section: Managing Fevermentioning
confidence: 98%
See 1 more Smart Citation
“…Fever was particularly detrimental on injury site metabolism when the peripheral white cell count was high, which suggests that fever associated with infection may be more detrimental than neurogenic fever. In 2 TSCI patient cohorts, managed in London and Berlin [57], high fever burden correlated with less neurological improvement. Though further studies are required to determine the effect and temporal relations between the different types of fever (infection, neurogenic) and injury site metabolism, based on the data to date, we suggest prompt treatment of fever in TSCI patients with paracetamol, nonsteroidal anti-inflammatory drugs, or active cooling.…”
Section: Managing Fevermentioning
confidence: 98%
“…Fever is observed in up to 67% of patients with acute TSCI and may arise from infection or be neurogenic [53][54][55][56]. In TSCI patients, fever was associated with significantly more deranged metabolite levels than normothermia evidenced by lower tissue glucose, higher lactate, higher glutamate, and higher lactate-to-pyruvate ratio (LPR, a measure of anaerobic metabolism) [57]. Fever was particularly detrimental on injury site metabolism when the peripheral white cell count was high, which suggests that fever associated with infection may be more detrimental than neurogenic fever.…”
Section: Managing Fevermentioning
confidence: 99%
“…100-fold changes in metabolite concentration, and 10-fold changes in LPR, compared with the preceding hour, were excluded. We previously showed that our MD method measures injury site surface metabolism, which correlates well with intraparenchymal metabolism (r = 0.56-0.91), but differs from metabolites measured from the lumbar cerebrospinal fluid (CSF) (r = 0.23-0.50) [16][17][18] .…”
Section: Cooling Cathetermentioning
confidence: 92%
“…The ISP probe and MD catheter were sutured to the skin. These techniques are described in detail in our earlier publications [16][17][18][19][20][21][22][23] .…”
mentioning
confidence: 99%
“…Following the primary injury, further cord damage may occur e.g. from ongoing cord compression, low blood pressure 5 , peripheral infections 6 and fever 7 .…”
Section: Introductionmentioning
confidence: 99%